High through-put sequencing of the Parhyale hawaiensis mRNAs and microRNAs to aid comparative developmental studies - Blythe, Martin J.; Malla, Sunir; Everall, Richard; Shih, Yu-huan; Lemay, Virginie; Moreton, Joanna; Wilson, Raymond; Aboobaker, Aziz (Public Library of Science, 2012)
Understanding the genetic and evolutionary basis of animal morphological diversity will require comparative developmental studies that use new model organisms. This necessitates development of tools for the study of genetics and also the generation of sequence information of the organism to be studied. The development of next generation sequencing technology has enabled quick and cost effective generation of sequence information. Parhyale hawaiensis has emerged as a model organism of choice due to the development of advanced molecular tools, thus P. hawaiensis genetic information will help drive functional studies in this organism.